2020
DOI: 10.1101/2020.12.18.20248483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of obesity on serum levels of SARS-CoV-2-specific antibodies in COVID-19 patients

Abstract: SARS-CoV-2 (Severe Acute Respiratory Syndrome Corona Virus-2), cause of COVID-19 (Coronavirus Disease of 2019), represents a significant risk to people living with pre-existing conditions associated with exacerbated inflammatory responses and consequent dysfunctional immunity. In this paper, we have evaluated the effects of obesity, a condition associated with chronic systemic inflammation, on the secretion of SARS-CoV-2-specific IgG antibodies in the blood of COVID-19 patients. Results have shown that SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The found correlation with older age reflects the stronger humoral inflammatory response reported in aged COVID-19 patients, which may hint at an impaired innate or cellular adaptive immune response [1,29]. Apart from older age, overweight has been described as an additional risk factor for severe COVID-19 progression usually linked with functional impairment of immune cells and decreased immunity as a result of chronic inflammation and hypercytokinemia [30,31]. Therefore, the observed positive association with higher anti-S/N and anti-S1 IgG levels may also be due to a unique predisposition of obese individuals to an impaired cellular anti-SARS-CoV-2 response and requires further investigation.…”
Section: Discussionmentioning
confidence: 91%
“…The found correlation with older age reflects the stronger humoral inflammatory response reported in aged COVID-19 patients, which may hint at an impaired innate or cellular adaptive immune response [1,29]. Apart from older age, overweight has been described as an additional risk factor for severe COVID-19 progression usually linked with functional impairment of immune cells and decreased immunity as a result of chronic inflammation and hypercytokinemia [30,31]. Therefore, the observed positive association with higher anti-S/N and anti-S1 IgG levels may also be due to a unique predisposition of obese individuals to an impaired cellular anti-SARS-CoV-2 response and requires further investigation.…”
Section: Discussionmentioning
confidence: 91%
“…Our results also show a decrease in NEFAs in the plasma of the COVID19 patients. In this regard, other researchers have reported a decrease ( Frasca et al, 2020 ; Thomas et al, 2020b ), and others an increase ( Shen et al, 2020 ) these results could be contradictory. However, the explanation could be, the dependance on the state of the infection process.…”
Section: Discussionmentioning
confidence: 73%
“…The SARS-CoV-2 pandemic has echoed the influenza virus A/H1N1 2009 pandemic in identifying obesity as a risk factor for severe disease and mortality ( 5 , 6 , 9 , 19 22 ). Several recent studies reported diminished antibody responses in individuals with obesity following coronavirus disease 2019 (COVID-19) vaccination ( 23 , 24 ). The current study investigated the hypothesis that the differences in vaccine-induced protection between obese and HW individuals may in part be driven by differences in their baseline and postvaccination influenza virus antibody repertoires.…”
Section: Discussionmentioning
confidence: 99%